2016
DOI: 10.1287/mnsc.2015.2285
|View full text |Cite
|
Sign up to set email alerts
|

Looking Across and Looking Beyond the Knowledge Frontier: Intellectual Distance, Novelty, and Resource Allocation in Science

Abstract: Selecting among alternative projects is a core management task in all innovating organizations. In this paper, we focus on the evaluation of frontier scientific research projects. We argue that the “intellectual distance” between the knowledge embodied in research proposals and an evaluator’s own expertise systematically relates to the evaluations given. To estimate relationships, we designed and executed a grant proposal process at a leading research university in which we randomized the assignment of evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
280
3
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(293 citation statements)
references
References 65 publications
8
280
3
2
Order By: Relevance
“…While it is possible that reviewers may have taken riskiness into account in their scores, they do not seem to be clearly expressing these concerns in their review comments. It is more likely that the bias is real and that reviewers are simply unaware of their risk aversion, as previous studies have documented the penalization of highly innovative work in a well-controlled peer review system (Boudreau et al 2016).…”
Section: Attitudes Toward Innovation and Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…While it is possible that reviewers may have taken riskiness into account in their scores, they do not seem to be clearly expressing these concerns in their review comments. It is more likely that the bias is real and that reviewers are simply unaware of their risk aversion, as previous studies have documented the penalization of highly innovative work in a well-controlled peer review system (Boudreau et al 2016).…”
Section: Attitudes Toward Innovation and Riskmentioning
confidence: 99%
“…Some have suggested that highly innovative research may be associated with more reviewer uncertainty about their judgments of the methodology, which may lead to lower scores (Luukkonen 2012;Boudreau et al 2016). While reviewers may consider innovation in their decisions, they likely give this less weight than methodological weaknesses, which is reflected in the content of the reviewer's critique.…”
Section: Attitudes Toward Innovation and Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing evaluation criteria are possible, which can lead to controversies (Engelhardt and Caplan 1987;Boudreau et al 2016). In the past few years, practitioners, the media, and many scientists have loudly complained that there is no mechanism by which inventors can guarantee the usability of academic findings (The Economist 2013;Freedman, Cockburn, and Simcoe 2015).…”
Section: Challenges In Navigating the Scientific Literaturementioning
confidence: 99%
“…Known negative biases include those driven by gender (Pohlhaus 2011;Tricco et al 2017), race (Ginther et al 2011), institution size (Murray et al 2016), geographic location (Wahls 2016), and interdisciplinary study (Bromham et al 2016). Additionally, Boudreau et al (2016) found a tendency for reviewers with a shorter intellectual distance from an application to provide harsher evaluations even when they were highly innovative. Other factors can also influence decision making, such as the bias towards the perceived value of high-income-country research (Harris et al 2017).…”
Section: The Process Is Biasedmentioning
confidence: 99%